THE INFLUENCE OF RUNNING DICTATION TECHNIQUE AND LEARNING MOTIVATION TOWARDS READING COMPREHENSION ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMPN 35 PALEMBANG - Nidya Aprisanti (Esteem Journal of English Education Study Programme, 2021)
This research was concerned with the influence of running dictation technique and learning motivation towards reading comprehension achievement of the eighth  grade students of SMPN 35 Palembang. In this study 60 students of eighth grade students of SMPN 35 Palembang in the academic year 2020/2021 were chosen as samples by means of two stage random sampling. This study applied factorial research design. The data were collected by using questionaire and test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test, and Two- Way ANOVA. From the two way ANOVA test results of 0.712 > 0.05, the results are obtained first, there was a significant influence in students’ reading comprehension taught by using running dictaton technique. Second, there was not any significant influence in students’ reading comprehension taught by conventional teaching technique. Third, there was significant influence in students’ reading comprehension students who have high and low learning motivation by using running dictation technique and conventional teaching technique. Last, there is not any significant interaction effects of motivation on students’ narrative text comprehension taught by using running dictation technique and learning motivation towards the students’ reading comprehension of SMPN 35 Palembang. So, running dictation technique was effective for students who have high and low learning motivation.